Up-conversion coding magnetic bead with red light emission, preparation method and application

By covalently bonding the carboxyl-modified upconversion nanoluminescent material with amino magnetic beads, red light upconversion encoded magnetic beads were prepared, which solved the background fluorescence and spectral interference problems of fluorescent-encoded microspheres, and improved stability and Specific, suitable for multi-objective bioassay and deep bioimaging.

CN119193140APending Publication Date: 2024-12-27INST OF SENSOR TECH GANSU ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411324332.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing fluorescent encoded microspheres have background fluorescence, spectral interference and stability problems of fluorescent substances during the preparation process, which limits their application in multi-target biological detection.

Method used

Using magnetic beads rich in amino functional groups with excellent performance as support, the carboxyl modified upconversion nanoluminescent material is combined by covalent bonding to prepare surface-covered red light upconversion fluorescent encoded magnetic beads to avoid non-special Adsorption of opposite sex and improves stability.

Benefits of technology

The uniformity and stability of fluorescence distribution are achieved, background signals are reduced, specificity is enhanced, and suitable for deep tissue imaging in the fields of multi-objective biodetection and biomedical science.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193140A_ABST
    Figure CN119193140A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biological magnetic beads, and relates to an up-conversion coding magnetic bead with red light emission, a preparation method and application, the up-conversion coding magnetic bead is prepared from an amino magnetic bead and an up-conversion material, the amino magnetic bead is coated with the up-conversion material, and the general formula of the up-conversion coding magnetic bead is Fe3O4 (at) SiO2-NH-CO-[NaErF4: Tm (at) NaYF4]; the up-conversion coding magnetic beads are spherical, good in dispersion and uniform in morphology and particle size, and the particle size is 5-6 microns; under the irradiation of 980nm laser, light emitted with 662nm as an emission center is very strong, and the up-conversion coding magnetic bead solution can be seen by naked eyes to present very strong red light. And the red light up-conversion material can be clearly seen from a laser confocal microscopy image and is uniformly distributed on the surface of the magnetic bead, which indicates that the up-conversion red light coding magnetic bead is successfully prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biological magnetic beads, and relates to up-conversion coded magnetic beads with red light emission, a preparation method and application thereof. Background Art

[0002] As the public's demand for health screening and physical examinations, and early warning and diagnosis of major diseases continues to rise, molecular diagnostic technology has attracted much attention. Liquid biochip technology is a new type of high-throughput detection technology for biomolecules that integrates flow analysis, coded microspheres, immunology, lasers and other technologies. It can achieve high-throughput, multi-component, and automated detection of biomolecules, providing a high-throughput technology platform for the new generation of molecular diagnosis. Fluorescent coded microspheres are one of the key core technologies of liquid biochips. The classification of detected substances is achieved by identifying microspheres with different coded signals through flow cytometry. Therefore, obtaining stable and accurate fluorescent coded microspheres is of great significance to improving the sensitivity of liquid biochip technology.

[0003] The inventor searched for research on the preparation of fluorescent coded microspheres and found that most of the reported fluorescent coded microspheres were prepared using the following methods. In terms of patents, the invention with application number 202310162551.7 first prepared monodisperse coated layered magnetic microspheres, and then swelled the organic fluorescent dye in the microspheres to prepare monodisperse superparamagnetic fluorescent coded microspheres. The invention with application number 202210743885.9 introduces magnetic nanoparticles and hydrophobic fluorescent dyes into porous carboxylated microspheres to prepare fluorescent coded magnetic beads. The invention with application number 201910415103.7 connects quantum dots or fluorescent dyes to magnetic microspheres, and then connects recognition molecules to prepare fluorescent coded magnetic beads. In the paper, Gu Hongchen's research group designed a strawberry-shaped host-guest dual-coding microsphere, which is composed of quantum dot-doped mesoporous polystyrene micron-sized host microspheres and thousands of nano-sized guest particles of organic fluorescent dyes (Adv. Funct. Mater. 2016, 26, 6146–6157). Zhu Ying et al. used micron-sized magnetic beads as host particles and used smaller fluorescent organic dye-doped silica nanoparticles as guest particles to prepare blueberry-shaped host-guest fluorescent coded magnetic beads (Chem. Commun., 2014,

[0004] 50,14041).

[0005] Although the above research has enriched the types of fluorescent coded microspheres and developed many preparation methods, the fluorescent substances organic fluorescein and quantum dots commonly used to prepare fluorescent coded microspheres are often accompanied by different degrees of background fluorescence, and the leakage of quantum dots in the microspheres and the light quenching induced by chemical substances also limit their use. In addition, the distance interval between the spectra of existing fluorescent coded microspheres is too narrow, the mutual interference is large, and the organic fluorescein is easily quenched and the quantum dots are easy to leak, which cannot effectively realize the detection of multiple targets. Therefore, the preparation of fluorescent microspheres with high stability, surface functionalization and the ability to couple biological molecules still faces great challenges.

[0006] Upconversion nanocrystals (UCNPs) are luminescent nanomaterials that convert near-infrared (NIR) excitation into visible emission through lanthanide doping, and provide high photochemical stability, sharp emission bandwidth and large anti-Stokes shift. Under infrared excitation, these upconversion nanocrystals have significant light penetration depth and no autofluorescence, making them ideal for luminescent probes in biomarkers and imaging techniques. Using upconversion luminescent materials with low background signals and high signal-to-noise ratios instead of organic fluoresceins and quantum dots can effectively avoid spectral interference and overlap between encoding signals and detection signals, improve the resolution of its fluorescence scanning, and thus improve the detection problems of existing fluorescent encoded microspheres. The inventors also searched for research on the preparation of upconversion fluorescent encoded microspheres. Wang Hanjie's research group encapsulated magnetic nanoparticles and upconversion nanocrystals into porous polystyrene microspheres (ACS Appl. Mater. Interfaces 2016, 8, 1, 745–753). Although this upconversion fluorescent encoded microsphere has good binding properties for biomolecules and rapid separation, the stability of the microspheres needs to be further improved.

[0007] In view of this, the present invention proposes to use magnetic beads rich in amino functional groups with excellent performance as carriers, and combine them with carboxyl-modified up-conversion nano-luminescent materials through covalent bonds to obtain surface-coated red light up-conversion fluorescent coded magnetic beads. The coded magnetic beads prepared by this method have good stability and uniformity, uniform fluorescence distribution, and can be coupled with biological molecules in the form of covalent bonds or streptavidin-biotin, with good stability, strong specificity, low background signal, low peak overlap, and can effectively avoid the occurrence of non-specific adsorption, which has great advantages in subsequent multi-target biological detection. The flow cytometers used for multi-target biological detection on the market are usually down-conversion excitation channels, and spectral interference and overlap phenomena will also occur. The up-conversion excitation channel can be obtained by instrument modification, so the up-conversion fluorescent coded magnetic beads prepared by us will play an important role in the improved flow cytometer. In addition, in the biomedical field, red light emitted in the range of 600-700nm is located in the "optical window" of biological tissue, can penetrate deep biological tissue, and the energy lost by scattering by biological tissue is also less than that of light of other wavelengths. Therefore, this red light emitting upconversion encoded magnetic beads also have good application prospects in biomedical fields such as biomarkers, cell imaging, and in vivo disease detection. Summary of the invention

[0008] The object of the present invention is to provide an up-conversion coded magnetic bead with red light emission and surface coated with an up-conversion material. The up-conversion coded magnetic bead is prepared from amino magnetic beads and an up-conversion material. The up-conversion material is coated on the amino magnetic beads. The general formula of the up-conversion coded magnetic bead is Fe3O4@SiO2-NH-CO-[NaErF4:Tm@NaYF4].

[0009] Preferably, the molar ratio of Er:Tm:Y in the up-conversion material NaErF4:Tm@NaYF4 is 0.996:0.004:0.1.

[0010] The second object of the present invention is to provide a method for preparing the up-conversion encoded magnetic beads, comprising the following steps:

[0011] (1) preparing an up-conversion material NaErF4:Tm@NaYF4, dispersing it in water, and setting aside;

[0012] (2) dispersing the amino magnetic beads in a 1,2-tetramethylenesulfonic acid solution containing Tween 20, and dropping the up-conversion material NaErF4:Tm@NaYF4 solution prepared in step (1) into the amino magnetic bead dispersion, and mixing by ultrasonication;

[0013] (3) Add a buffer solution containing 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to the solution obtained in step (2) and mix well; wash three times with sodium hydroxide solution and water respectively to remove excess up-conversion material, thereby obtaining up-conversion red light coded magnetic beads Fe3O4@SiO2-NH-CO-[NaErF4:Tm@NaYF4].

[0014] Preferably, the upconversion material NaErF4:Tm@NaYF4 described in step (1) is a carboxylated upconversion material NaErF4:Tm@NaYF4.

[0015] Preferably, the carboxylated upconversion material NaErF4:Tm@NaYF47-8 mg described in step (1) is dispersed in 800 μL of water.

[0016] Preferably, the upconversion material NaErF4:Tm@NaYF4 described in step (1) is prepared by the following method:

[0017] S1) Dissolve the Er-containing 3+ and Tm 3+ The compound solution was added to the mixed solution containing oleic acid and octadecene, stirred at room temperature, slowly heated to 110°C, kept for 1 hour, heated to 160°C under nitrogen atmosphere, and heated for another 1 hour;

[0018] S2) the solution obtained in step S1) is cooled to 50°C, 10 mL of a methanol solution containing ammonium fluoride and sodium hydroxide is added, and after stirring at 50°C for 1 hour, the temperature is increased to 70°C to remove methanol;

[0019] S3) evaporating the methanol in the solution obtained in step (2), heating to 110° C., storing under a nitrogen atmosphere for 1 h to remove residual oxygen and water, heating to 290-300° C., storing for 1-1.5 h; precipitating the product with ethanol, collecting by centrifugation, washing with ethanol and cyclohexane to obtain NaErF4:Tm core nanoparticles, dispersing with cyclohexane for later use;

[0020] S4) adding hydrated yttrium chloride dissolved in deionized water to a flask containing oleic acid and 1-octadecene, slowly heating to 150° C., storing for 1.5 h, cooling to 50° C., adding the NaErF4:Tm cyclohexane solution prepared in step S3), stirring, and evaporating the cyclohexane;

[0021] S5) Cool the solution obtained in step S4) to 50°C, add a methanol solution containing ammonium fluoride and sodium hydroxide, and stir at 50°C for 15 minutes; heat to 110°C under a nitrogen atmosphere and store for 1 hour; increase the temperature to 290-300°C and store for 1 hour, wash the obtained product with ethanol and cyclohexane, and disperse it in cyclohexane to obtain a cyclohexane solution of NaErF4:Tm@NaYF4.

[0022] The third object of the present invention is to provide the use of the up-conversion encoded magnetic beads in the preparation of preparations for fluorescent in vivo imaging.

[0023] The fourth object of the present invention is to provide the use of the up-conversion encoded magnetic beads in the preparation of cell imaging reagents and biomarker reagents.

[0024] The present invention has the following beneficial effects:

[0025] The present invention provides an up-conversion coded magnetic bead with red light emission and coated with up-conversion material on the surface, wherein the up-conversion coded magnetic bead is spherical, well dispersed, uniform in morphology and particle size, and has a particle size of 5-6 μm; under 980 nm laser irradiation, the light emitted with 662 nm as the emission center is very strong, and the up-conversion coded magnetic bead solution can be seen by the naked eye to present very strong red luminescence, and the red light up-conversion material can also be clearly seen from the laser confocal microscope image to be evenly distributed on the surface of the magnetic bead. This up-conversion coded magnetic bead has good stability and fluorescence uniformity, strong specificity, can be coupled with biological molecules, low background signal, low peak overlap, and can effectively avoid the occurrence of non-specific adsorption, and has great advantages in subsequent multi-target biological detection. In addition, the red light located in the "optical window" of biological tissue can penetrate deep biological tissue with little energy loss, so this red light-emitting up-conversion coded magnetic bead also has good application prospects in biomedical fields such as biomarkers, cell imaging, and in vivo disease detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images (ab images) and corresponding energy dispersive X-ray spectroscopy (EDX) images (cf images) of NaErF4:Tm material; High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images (g images) and corresponding energy dispersive X-ray spectroscopy (EDX) images (hl images) of NaErF4:Tm@NaYF4 red light upconversion material;

[0027] Figure 2 This is the fluorescence spectrum of up-converted red light coded magnetic beads;

[0028] Figure 3The scanning electron microscope images (a-b), X-ray diffraction images (c) and infrared spectra (d) of amino magnetic beads are shown;

[0029] Figure 4 This is a scanning electron microscope image (SEM) of up-converted red light encoded magnetic beads;

[0030] Figure 5 This is a confocal laser scanning microscopy (CLSM) image of up-converted red light coded magnetic beads;

[0031] Figure 6 This is a fluorescence photograph of up-conversion red light coded magnetic beads under 980nm laser excitation. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. The following examples are only used to illustrate the technical solution of the present invention but are not intended to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should all be included in the scope of the claims of the present invention.

[0033] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.

[0034] In the following examples, the methods used are conventional methods; the reagents used can all be purchased from the market.

[0035] Example 1. Preparation of up-conversion red light coded magnetic beads

[0036] (1) Dissolve 1 mmol of Er in 2 mL of water. 3+ and Tm 3+ The compound solution was added to a mixed solution containing 6 mL of oleic acid and 15 mL of octadecene, stirred at room temperature for 20 min, slowly heated to 110 °C, stored for 1 h, heated to 160 °C under a nitrogen atmosphere, and heated for another 1 h;

[0037] (2) The solution obtained in step (1) was cooled to 50°C, 10 mL of a methanol solution containing ammonium fluoride (148 mg, 4 mmol) and sodium hydroxide (100 mg, 2.5 mmol) was added, and after stirring at 50°C for 1 h, the temperature was raised to 70°C to remove methanol;

[0038] (3) After evaporating the methanol in the solution obtained in step (2), the solution was heated to 110° C. and stored in a nitrogen atmosphere for 1 h to remove residual oxygen and water, and then heated to 300° C. and stored for 1 h; the product was precipitated with ethanol, collected by centrifugation at 10,000 rpm for 10 min, and washed several times with ethanol and cyclohexane to obtain NaErF4:Tm core nanoparticles (as seeds for the growth of the inert shell), which were dispersed with 10 mL of cyclohexane for later use;

[0039] (4) Add hydrated yttrium chloride (YCl3·6H2O) (30.34 mg, 0.1 mmol) dissolved in 2 mL of deionized water into a 100 mL flask containing 6 mL of oleic acid and 15 mL of 1-octadecene, slowly heat to 150° C., store for 1.5 h, cool to 50° C., add 10 mL of the NaErF4:Tm cyclohexane solution prepared in step (3), stir at 90° C. for 20 min, and evaporate the cyclohexane;

[0040] (5) The solution obtained in step (4) was cooled to 50°C, 10 mL of a methanol solution containing ammonium fluoride (148 mg, 4 mmol) and sodium hydroxide (100 mg, 2.5 mmol) was added, and the mixture was stirred at 50°C for 15 min; the mixture was heated to 110°C under a nitrogen atmosphere and stored for 1 h (to remove residual oxygen and water); the temperature was increased to 290°C and stored for 1 h. The obtained product was washed several times with ethanol and cyclohexane, and dispersed in cyclohexane to obtain a cyclohexane solution of NaErF4:Tm@NaYF4 for later use;

[0041] (6) Add 0.5 g of polyacrylic acid (PAA) to 20 mL of diethylene glycol, heat to 110° C., and stir vigorously under nitrogen; inject 2 mL of the cyclohexane solution of NaErF4:Tm@NaYF4 obtained in step (5), heat to 230° C., and store for 1 hour; after cooling to room temperature, add an excess of dilute hydrochloric acid aqueous solution, centrifuge to obtain a white powder, and wash the powder three times with pure water to obtain a carboxylated NaErF4:Tm@NaYF4 upconversion material that is well dispersed in water;

[0042] (7) 3 mg of amino magnetic beads were dispersed in 300 μL of 10 mM ethyl sulfonic acid (MES) solution containing 0.05% Tween 20, 8 mg of the carboxylated NaErF4:Tm@NaYF4 upconversion material obtained in step (6) was dispersed in 800 μL of water, and then added dropwise to the amino magnetic bead dispersion, ultrasonicated for 5 min, and then placed in a vortex mixer and rotated for 5 min;

[0043] (8) Add 200 μL of a buffer solution containing 10 mg 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and 10 mg N-hydroxysuccinimide (NHS) to the solution obtained in step (7), and rotate in a vortex mixer for 3 h; wash three times with sodium hydroxide solution (0.1 M) and water respectively to remove excess upconversion material, thereby obtaining upconversion red light encoded magnetic beads Fe3O4@SiO2-NH-CO-[NaErF4:Tm@NaYF4].

[0044] The high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images of the prepared NaErF4:Tm material and NaErF4:Tm@NaYF4 red light upconversion material and the corresponding energy dispersive X-ray spectroscopy imaging (EDX) images are shown in Figure 2. Figure 1 The HAADF-STEM image and EDX image of NaErF4:Tm show that the NaErF4:Tm material is spherical, and Er, F, Na and Tm are well distributed ( Figure 1 af); Figure 1 gl is the HAADF-STEM image and EDX image of the prepared NaErF4:Tm@NaYF4 red light upconversion material, showing that the NaErF4:Tm@NaYF4 red light upconversion material is a core-shell type, indicating the presence of Er, F, Na, Tm and Y and that the outer coating layer is NaYF4.

[0045] Figure 2 This is the fluorescence spectrum of the up-conversion red light encoded magnetic beads. It can be seen from the figure that under the irradiation of 980nm laser, the light emitted with 662nm as the emission center is very strong.

[0046] The scanning electron microscope image, X-ray diffraction image and infrared spectrum of the amino magnetic beads used in this example are as follows: Figure 3 shown. Figure 3 The scanning electron microscopy images of ab show that the amino magnetic beads are well dispersed, with uniform morphology and particle size, and the diameter of the beads is 5-6μm. Figure 3 The X-ray diffraction pattern of c amino magnetic beads can be seen to be consistent with the standard diffraction spectrum of inverse spinel Fe3O4 (JCPDS.19-0629). In addition, an amorphous polymer coating peak appears at a diffraction angle of about 20.00°, indicating that the surface of the magnetic beads is coated with a polymer. Figure 3 In the infrared spectrum of d, curve a is the infrared spectrum of silica-coated magnetic beads (Fe3O4@SiO2), and curve b is the infrared spectrum of amino magnetic beads (Fe3O4@SiO2-NH2). -1 The peak at 1250-1200cm is the peak of Si-O-Si bond. -1The peak at 673 cm is the peak of Si-CH2-R bond. -1 The peak at 1510 cm is the NH bond bending vibration peak. -1 The peak at -NH3 + The bending vibration peaks further indicate the presence of amino groups.

[0047] Figure 4 This is a scanning electron microscope image of up-conversion red light encoded magnetic beads. It can be seen that a large amount of up-conversion material is loaded on the surface of the amino magnetic beads, and the morphology and particle size of the up-conversion red light encoded magnetic beads are uniform and have good dispersion.

[0048] from Figure 5 It can also be clearly seen from the laser confocal microscopy image that the red light upconversion material is evenly distributed on the surface of the magnetic beads, indicating that the upconversion red light encoded magnetic beads have been successfully prepared.

[0049] Example 2-6, Preparation of up-conversion red light coded magnetic beads

[0050] The preparation method of the surface-coated upconversion fluorescent coded magnetic beads comprises the following steps:

[0051]

[0052] By characterizing the up-conversion red light coded magnetic beads prepared in Examples 2-6, it can be found that up-conversion red light coded magnetic beads with good performance can be prepared under the above reaction temperature and reaction time. Figure 6 This is a fluorescence photograph of the up-conversion red light encoded magnetic beads prepared in Example 2-6 under 980nm laser excitation.

[0053] In summary, the present invention provides an up-conversion coded magnetic bead with red light emission and coated with an up-conversion material on the surface. The up-conversion coded magnetic bead is spherical, well dispersed, uniform in morphology and particle size, and has a particle size of 5-6 μm. Under 980 nm laser irradiation, the light emitted with 662 nm as the emission center is very strong, and the naked eye can see that the up-conversion coded magnetic bead solution presents very strong red light emission. It can also be clearly seen from the laser confocal microscope image that the red light up-conversion material is evenly distributed on the surface of the magnetic bead, indicating that the up-conversion red light coded magnetic bead has been successfully prepared.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An up-conversion coded magnetic bead with red light emission, characterized in that, The up-conversion encoded magnetic beads are prepared from amino magnetic beads and up-conversion materials. The up-conversion materials are coated on the amino magnetic beads. The general formula of the up-conversion encoded magnetic beads is Fe3O4@SiO2-NH-CO-[NaErF4:Tm@NaYF4].

2. The up-conversion coded magnetic bead according to claim 1, characterized in that: The molar ratio of Er:Tm:Y in the up-conversion material NaErF4:Tm@NaYF4 is 0.996:0.004:0.

1.

3. The method for preparing up-conversion encoded magnetic beads according to claims 1 and 2, characterized in that: The steps include: (1) preparing an up-conversion material NaErF4:Tm@NaYF4, dispersing it in water, and setting aside; (2) dispersing the amino magnetic beads in a 1,2-tetramethylenesulfonic acid solution containing Tween 20, and dropping the up-conversion material NaErF4:Tm@NaYF4 solution prepared in step (1) into the amino magnetic bead dispersion, and mixing by ultrasonication; (3) Add a buffer solution containing 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to the solution obtained in step (2) and mix well; wash three times with sodium hydroxide solution and water respectively to remove excess up-conversion material, thereby obtaining up-conversion red light coded magnetic beads Fe3O4@SiO2-NH-CO-[NaErF4:Tm@NaYF4].

4. The method for preparing up-conversion encoded magnetic beads according to claim 3, characterized in that: The upconversion material NaErF4:Tm@NaYF4 described in step (1) is a carboxylated upconversion material NaErF4:Tm@NaYF4.

5. The method for preparing up-conversion encoded magnetic beads according to claim 4, characterized in that: The carboxylated upconversion material NaErF4:Tm@NaYF47-8 mg described in step (1) is dispersed in 800 μL of water.

6. The method for preparing up-conversion encoded magnetic beads according to claim 3, characterized in that: The up-conversion material NaErF4:Tm@NaYF4 described in step (1) is prepared by the following method: S1) Dissolve the Er-containing 3+ and Tm 3+ The compound solution was added to the mixed solution containing oleic acid and octadecene, stirred at room temperature, slowly heated to 110°C, kept for 1 hour, heated to 160°C under nitrogen atmosphere, and heated for another 1 hour; S2) the solution obtained in step S1) is cooled to 50°C, 10 mL of a methanol solution containing ammonium fluoride and sodium hydroxide is added, and after stirring at 50°C for 1 hour, the temperature is increased to 70°C to remove methanol; S3) evaporating the methanol in the solution obtained in step (2), heating to 110° C., storing under a nitrogen atmosphere for 1 h to remove residual oxygen and water, heating to 290-300° C., storing for 1-1.5 h; precipitating the product with ethanol, collecting by centrifugation, washing with ethanol and cyclohexane to obtain NaErF4:Tm core nanoparticles, dispersing with cyclohexane for later use; S4) adding hydrated yttrium chloride dissolved in deionized water to a flask containing oleic acid and 1-octadecene, slowly heating to 150° C., storing for 1.5 h, cooling to 50° C., adding the NaErF4:Tm cyclohexane solution prepared in step S3), stirring, and evaporating the cyclohexane; S5) Cool the solution obtained in step S4) to 50°C, add a methanol solution containing ammonium fluoride and sodium hydroxide, and stir at 50°C for 15 minutes; heat to 110°C under a nitrogen atmosphere and store for 1 hour; increase the temperature to 290-300°C and store for 1 hour, wash the obtained product with ethanol and cyclohexane, and disperse it in cyclohexane to obtain a cyclohexane solution of NaErF4:Tm@NaYF4.

7. Use of the up-conversion encoded magnetic beads as claimed in claim 1 in the preparation of a preparation for fluorescent in vivo imaging.

8. Use of the up-conversion encoded magnetic beads as claimed in claim 1 in the preparation of cell imaging reagents and biomarker reagents.

Citation Information

Patent Citations

  • Fluorescent encoded magnetic bead and preparation and application thereof

    CN110187115A

  • Preparation method of fluorescence coding magnetic beads based on liquid phase chip technology

    CN115165711A

  • Monodisperse superparamagnetic fluorescent encoding microsphere, preparation method and application

    CN116143964A